Crystal structure of (E)-1-(3,4-dimethoxyphenyl)-3-(dimethylamino)prop-2-en-1-one, C13H17NO3 - Ghorab Mostafa M.; Alsaid Mansour S.; Ghabbour Hazem A.; Fun Hoong-Kun (Zeitschrift für Kristallographie - New Crystal Structures, 2016)
C13H17NO3, monoclinic, P21/c, a = 7.7486(4) Å, b = 8.5148(3) Å, c = 19.9822(9) Å, β = 100.341(2)°, V = 1296.97(10) Å3, Z = 4, Rgt(F) = 0.0620, wRref(F2) = 0.1814, T = 296 K.